Pioneering of Schools with International Standard to Respond the Globalization - Ipnugraha Ipnugraha (Journal of Education and Learning (EduLearn), 2013)
In order to meet respond the challenges of globalization Indonesia Government held a Pioneering of Schools with International Standard (RSBI). As an international standard schools pilot, these schools prepared gradually through the guidance by government and stakeholders. Within a certain period of four years it is expected that the schools is able to fulfill and meet the criteria of Schools with International Standard (SBI). Actually, in it’s implementation, RSBI faces many challenges, among others, were expensive anda require modern infrastructure, require a qualified teacher, SBI criteria and English implementation in education not yet possessed constitutional base. With RSBI it will form a national school with national education standards that have international quality and its graduates are able to compete internationally